PERAN DAKWAH MELALUI BIMBINGAN DAN KONSELING DALAM MEMBINA KEHARMONISAN RUMAH TANGGA - Suriati Suriati (Komunitas Dosen Dakwah Institut Agama Islam Negeri (IAIN) Palu, 2013)
Da'wah has many forms. One of them is guidance and counseling. but da'wah in the form of guidance and counseling is still not so often performed. Preachers more oriented preaching in the pulpit or on takllm assemblies. Though not all people problem be missed through such forms of da'wah. Guidance and counseling is one of the techniques in solving people's problems, especially problems of households. Through guidance and counseling, domestic harmony can be achieved by every Muslim family. guidance and counseling should try and take on the role to foster harmony in the household, including the development of a state trying to do a better direction, healing, repair, and maintenance of household Islam by using approaches and techniques in guidance and counseling.